INVESTIGATION OF SPORTS FACILITIE'S IN TERMS OF QUANTITIES AND QUALITIES IN PRIMARY AND SECONDARY SCHOOLS IN ELAZIG CITY CENTER - Eyyup Nacar (ümit doğan üstün, 2019)
By determining the current situation of Sports facilities located in the units providing sports education in secondary education institutions in terms of quality and quantity, the aim is to be investigated the use of physical education and sports training facilities of sports facilities in terms of physical education teachers by using their fields of study and competence and capacity levels in line with the curriculum. Research; A total of 169 schools including 62 primary schools, 59 secondary schools and 48 high schools in the province of Elazığ, and for this research 353 physical education teachers working in these schools have been participated. In the data obtained, SPSS 17.0 package program is used and the percentage, frequency test are applied and the results are presented with tables. As a result, It has been determined that the existing sports facilities in the primary and secondary schools in Elazığ city center are insufficient in terms of quality and quantity.